2022
DOI: 10.1097/hm9.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Campanumoea javanica Bl. activates the PI3K/AKT/mTOR signaling pathway and reduces sarcopenia in a T2DM rat model

Abstract: Objective: Sarcopenia causes loss of skeletal muscle and function, thus seriously affecting the physical function and quality of life in the elderly. This article discusses the specific molecular mechanism and ameliorating effects of Tudangshen (TDS) on sarcopenia in elderly rats with type 2 diabetes mellitus (T2DM).Methods: Elderly Sprague-Dawley (SD) rats were randomly selected and fed with a high-fat diet combined with an intraperitoneal injection of streptozotocin to establish T2DM model. The model rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The previous study showed that examining the effects of nanogels on cytokine levels was worthwhile for immune systems induced by immune stimulators [ 32 ]. Natural active compounds have been widely used in treating diseases due to their low toxicity and good biocompatibility [ 33 35 ]. To investigate whether quercetin nanogels had immunostimulatory effects, TNF-α and IL-6 concentrations in the cell supernatant were determined after incubation with RAW 264.7 cells for 48 h. Compared with the control, quercetin nanogels and blank nanogels did not stimulate RAW 264.7 cells to secrete excessive inflammatory factors (Figure S2 c-d), indicating that the quercetin nanogels and blank nanogels did not activate the cellular immune response.…”
Section: Resultsmentioning
confidence: 99%
“…The previous study showed that examining the effects of nanogels on cytokine levels was worthwhile for immune systems induced by immune stimulators [ 32 ]. Natural active compounds have been widely used in treating diseases due to their low toxicity and good biocompatibility [ 33 35 ]. To investigate whether quercetin nanogels had immunostimulatory effects, TNF-α and IL-6 concentrations in the cell supernatant were determined after incubation with RAW 264.7 cells for 48 h. Compared with the control, quercetin nanogels and blank nanogels did not stimulate RAW 264.7 cells to secrete excessive inflammatory factors (Figure S2 c-d), indicating that the quercetin nanogels and blank nanogels did not activate the cellular immune response.…”
Section: Resultsmentioning
confidence: 99%
“…Sex hormones play a key role in the occurrence and development of EC 67 . Studies have shown that excessive endogenous estrogen may directly stimulate the growth of endometrium by activating estrogen receptors α and play a carcinogenic role by activating insulin‐like growth factor (IGF) receptor 1 and epidermal growth factor receptor, thereby activating the downstream PI3K‐AKT–mTOR pathway 68‐70 …”
Section: Discussionmentioning
confidence: 99%
“…67 Studies have shown that excessive endogenous estrogen may directly stimulate the growth of endometrium by activating estrogen receptors α and play a carcinogenic role by activating insulin-like growth factor (IGF) receptor 1 and epidermal growth factor receptor, thereby activating the downstream PI3K-AKT-mTOR pathway. [68][69][70] Furthermore, in amino acid metabolism, amino acid levels in healthy individuals are usually controlled within a certain range by the homeostatic function of the organism. 71 Studies have shown that various amino acid levels of patients with different types of gynaecological cancer may be changed.…”
Section: Mechanism Of Related Metabolic Pathways In Ecmentioning
confidence: 99%
“…However, this conclusion needs further verification by prospective cohort studies in the future. TCM emphasizes improving symptoms and preventing secondary complications ( Zheng et al, 2020 ; Chen et al, 2022 ; Zuo et al, 2022 ). Unlike TCM, Western therapies focus on blood glucose regulation and cardiovascular risk factor management in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%